THE DAILY LIFE OF POST-STROKE PATIENTS IN TOMOHON CITY, NORTH CELEBES, INDONESIA - Rayanti, Rosiana E.; Karwur, Juliana D.; Karwur, Ferry F. (Silliman Journal, 2022)
Stroke, in this case paralytic stroke, is a sudden paralysis caused by a brain injury. As a result of paralysis, post-stroke patients will have physical, psychological and social limitations that affect their quality of life. As a consequence, patients need help from others, especially from their family to go through their daily activities. This study aimed to show the prevalence and characteristics of poststroke patients and describe their daily life pattern of activities in Tomohon City, Indonesia. Data were collected through in-depth interviews with observations from five participants of family members who had experienced stroke. Results of this study indicated changes in the life of post-stroke patients in terms of their daily activities, eating habits, and family communication patterns. As a result of physical weakness the daily life of the five participants was limited only to home activities. Food preference and consumption were also affected. Both participants and caregivers perceived that the emotional sensitivity they had developed and the changes in terms of family roles frequently led to misunderstandings between the patients and the caregivers.